PEMEROLEHAN BAHASA - Sundari, Weli (Jurnal Warna, 2018)
This research is motivated about how humans get their first language discussed among researchers. This theory states that human beings get their first language naturally. Language acquisition is a process that takes place inside a child's brain when he or she gets his first language or his mother tongue. Language acquisition is different from language learning. Language learning deals with the processes that occur when a child learns a second language after he or she gets his first language. Thus, language acquisition is related to the first language, while language learning is related to the second language. Theories of language acquisition are: (1) The theory of Behaviorism (2) Nativistic Theory (3) Theory of Cognitivism (4) Theory of Interactionism. The results obtained in this study (1) The acquisition of the first language is closely related to the child's cognitive development. From the research of experts on cognitive development can be drawn two conclusions namely the production of speech-based speech that is regular but not automatically and the speaker must obtain cognitive categories underlying the meaning of expressive natural language.